2010
DOI: 10.1007/s10750-009-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen retention by peatland buffer areas at six forested catchments in southern and central Finland

Abstract: We studied the nitrogen retention capacity of six peatland buffer areas constructed in forested catchments in southern and central Finland. The buffers (0.1-4.9% of the total catchment area) were either undrained mires or drained peatlands rewetted 4-7 years before the present study. The N retention capacity was studied by adding ammonium nitrate (NH 4 NO 3 -N) solution into the inflow waters of the buffers once (one area) or twice (five areas) during a period of 4-6 years. Except for the first N addition in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 18 publications
(38 reference statements)
0
42
0
Order By: Relevance
“…Diffuse nutrient pollution has been found to be a major obstacle to this goal. As nitrate is effectively reduced under wet conditions (Cabezas et al, 2012), re-wetting peatlands has been suggested as a measure to both reduce diffuse pollution originating from degraded peatlands themselves and to clean nutrient-rich water from upstream areas (Davidsson et al, 2002;Trepel, 2010;Vikman et al, 2010). Especially strongly degraded peat seems to have a high denitrification and N retention potential when re-wetted (Cabezas et al, 2012;Davidsson et al, 2002), although other studies have found ongoing mineralisation under these conditions (Olde Venterink et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse nutrient pollution has been found to be a major obstacle to this goal. As nitrate is effectively reduced under wet conditions (Cabezas et al, 2012), re-wetting peatlands has been suggested as a measure to both reduce diffuse pollution originating from degraded peatlands themselves and to clean nutrient-rich water from upstream areas (Davidsson et al, 2002;Trepel, 2010;Vikman et al, 2010). Especially strongly degraded peat seems to have a high denitrification and N retention potential when re-wetted (Cabezas et al, 2012;Davidsson et al, 2002), although other studies have found ongoing mineralisation under these conditions (Olde Venterink et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The sites receive outflow water from the surrounding forested catchment (29,36). Restoration of the drained peatlands was carried out 10 to 12 years before our study by filling in the drainage ditches with peat.…”
mentioning
confidence: 99%
“…At present, spruce swamp forests are also restored in protected areas on private land and in commercial forests (Government of Finland 2008). Concurrently, spruce swamp forests have been experimentally rewetted to be used as buffer zones for runoff waters from areas of intensive forestry to reduce concentrations of organic matter, nitrogen and phosphorus (Nieminen et al 2005ab, Väänänen et al 2008, Vikman et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…If rewetting ceases the high CO2 emissions from old peat measured in drained sites (Ojanen et al 2013), significant carbon benefits are expected -but only if the decreased CO2 emissions are not counteracted by increased CH4 emissions from the blocked ditches and other new wet habitats (Cooper et al 2014, Koskinen et al 2012. Spruce swamp forests rewetted as buffer zones for runoff waters have functioned as efficient sinks for dissolved organic matter (Nieminen et al 2005b) and, after more than six years after rewetting, for phosphorus (Väänänen et al 2008) and nitrogen (Vikman et al 2010). During the first (seven) years after rewetting though, rewetting of spruce swamp forest may increase leaching of phosphorus, nitrogen and total organic carbon (Nieminen et al 2005a, Koskinen et al 2011.…”
Section: Introductionmentioning
confidence: 99%